Clinical and Laboratory Manifestation of Children with Acute Lymphoblastic Leukemia as an Assessment of Severity: A Study in Dr. Hasan Sadikin General Hospital - Yohana Kusuma Angkasa; Nur Suryawan; Delita Prihatni (Faculty of Medicine Universitas Padjadjaran, 2019)
Background: Acute lymphoblastic leukemia (ALL) is a disease caused by a mutation of lymphoid progenitor cells in bone marrow, that induces uncontrolled lymphoid cell proliferation. ALL is the most common type of leukemia in children. Various clinical and laboratory manifestation makes the diagnostic process more complicated. This study aimed to observe the clinical and laboratory manifestation of children with ALL in Dr. Hasan Sadikin General Hospital for diagnostic and assessment.Methods: The design of this study was a descriptive cross-sectional with a total sampling method. Data of all children under 18 years old with ALL diagnosed in 2015 to 2017 were included. The diagnosis of ALL was confirmed by examination of hematology indices, peripheral blood smear, and bone marrow aspiration classified by FAB. Inaccessible or incomplete medical records were excluded.Results: In total, 192 data of ALL patients were included. Most ALL patients predominantly occurred in boys (59.9%), and the age group of 1–5 years old (40.6%). The clinical manifestations were pallor (89.6%), hepatomegaly (79.7%) and fever (75%). Most patients experienced severe anemia with hemoglobin level <7g/dL (44.8%), leukocytosis >20.000 cells/mm3 (46.9%), severe thrombocytopenia with platelet count <20.000 cells/mm3 (51%), and blast cells count >50% (45.3%). Based on FAB classification, the majority of the patients were classified as ALL type L2 (65.6%).Conclusions: Clinical and laboratory manifestation of ALL patients can be used as a parameter for diagnostic and assessment of severity. Earlier diagnosis would result in better prognosis and more precise treatment for ALL patients.